Teaching priorities and wealth of our turkish - Güneş, Firdevs (T.C. Milli Egitim Bakanligi, 2016)
In our World, there has been a deep and silent war among major languages for long years. This war initially started based on superiority claims and then changed into becoming the language of education, science, trade, communication and internet in time. Based on all of the criteria of language wars, Western languages have been come forward and their superiority has been claimed. The claim that our Turkish was hard and difficult to learn, not sufficient and not science language was stated. However, the new research in language has showed that this claim is not accurate and agglutinative languages are easy to learn. The research about brains also illustrate that Turkish is suitable for the working system of brain and facilitates learning process. The properties of Turkish such as richness of sound, the relationship between sound and letter, derivation of syllable and word, identification of word and developing mental dictionary facilitate teaching literacy and improve mental skills. In Turkish in which each sound is written by a letter, the words that are heard can be very quickly transferred into writing. Ornamentation words are not mostly used in Turkish texts different from western languages and many meanings and information are transferred by a few words. These properties provide various priorities for our Turkish and it can be learned more early then other languages. © 2017 Elsevier B.V., All rights reserved.
TÜRKÇENİN ÖĞRETİM ÜSTÜNLÜKLERİ VE ZENGİNLİKLERİ
Keywords: Priority; Teaching; Turkish; Wealth